Answer:
n = (-5)/13
Explanation:
Solve for n:
4 (5 n + 1) - 8 = -6 n - 14
4 (5 n + 1) = 20 n + 4:
20 n + 4 - 8 = -6 n - 14
Add like terms. 4 - 8 = -4:
20 n - 4 = -6 n - 14
Add 6 n to both sides:
20 n + 6 n - 4 = (6 n - 6 n) - 14
6 n - 6 n = 0:
20 n + 6 n - 4 = -14
20 n + 6 n = 26 n:
26 n - 4 = -14
Add 4 to both sides:
26 n + (4 - 4) = 4 - 14
4 - 4 = 0:
26 n = 4 - 14
4 - 14 = -10:
26 n = -10
Divide both sides of 26 n = -10 by 26:
(26 n)/26 = (-10)/26
26/26 = 1:
n = (-10)/26
The gcd of -10 and 26 is 2, so (-10)/26 = (2 (-5))/(2×13) = 2/2×(-5)/13 = (-5)/13:
Answer: n = (-5)/13